ASSESSMENT OF SURGICAL TREATMENT STRATEGIES OF IATROGENIC GIANT FEMORAL ARTERY PSEUDOANEURYSMS - YAQOOB , RA; MUSTAFA , MA; ZAFAR , GM; JAVAID , MAA; BUTT , UB (Biological and Clinical Sciences Research Journal, 2024)
Iatrogenic giant femoral artery pseudoaneurysms pose significant clinical challenges, necessitating prompt intervention to prevent complications. Despite advancements in endovascular techniques, optimal surgical strategies remain unclear. This study aimed to evaluate surgical treatment's technical and clinical outcomes for these pseudoaneurysms. Objective: To assess the technical success and clinical outcomes following surgical repair of iatrogenic giant femoral artery pseudoaneurysms. Methods: This retrospective cohort study was conducted at a tertiary care hospital in Lahore, Pakistan between July 2022 and July 2023. A total of 60 patients diagnosed with iatrogenic giant femoral artery pseudoaneurysms underwent surgical repair. It was followed up for one, three, and six months using Duplex ultrasound and CT angiography. Data were analyzed to evaluate surgical techniques, technical success rates, and postoperative outcomes. Statistical analysis was performed using descriptive statistics and chi-square tests. Results: All patients (n=60) underwent successful surgical repair with various techniques: primary repair (n=30), repair with vein patch angioplasty (n=15), interposition reversed saphenous vein graft (n=10), and interposition synthetic Dacron graft (n=5). Technical success was achieved in 100% of cases, with no limb loss or intraoperative/postoperative mortality. The presenting symptoms were resolved in all patients, with one case of postoperative groin wound infection being effectively managed with antibiotics and debridement. Conclusion: Open surgical repair of femoral pseudoaneurysms demonstrates excellent technical feasibility and serves as a first-line treatment for iatrogenic giant femoral artery pseudoaneurysm-associated complications. These findings support surgical intervention as a practical approach to managing these challenging cases.